Sensitivity Plot of cy:{(m4 + 3* m2)*10-4} - Cycle of Money - Challoumis, Constantinos (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
In this work, financial liquidity predominates over escape savings. The velocity of financial liquidity is twice as high as the velocity of escape savings. It uses mathematical definitions by the cycle of money and shows the sensitivity plot of cy: {(m4 + 3*m2)*10-4}. In this case, financial liquidity is identical to the cycle of money. The applied methodology is the S.M. (Sensitivity Method).